2020
DOI: 10.3390/ma13194349
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Implant Geometry and Primary Stability in Different Bony Defects and Variant Bone Densities: An In Vitro Study

Abstract: Aim: This in vitro study aimed to evaluate the effects of implant designs on primary stability in different bone densities and bony defects. Methods: Five implant types (tapered-tissue-level, tissue-level, zirconia-tissue-level, bone-level, and BLX implants) were used in this assessment. The implants were inserted into four different artificial bone blocks representing varying bone-density groups: D1, D2, D3, and D4. Aside from the control group, three different types of defects were prepared. Using resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…It has been proclaimed that its double thread design could provide an improved initial stability in all types of bone through uniform and controlled compaction and densification of the peri-implant bone [ 26 ]. The number of studies focusing on the primary stability of this novel system is limited [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proclaimed that its double thread design could provide an improved initial stability in all types of bone through uniform and controlled compaction and densification of the peri-implant bone [ 26 ]. The number of studies focusing on the primary stability of this novel system is limited [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the variety of implant designs included in this study, it was difficult to draw a definitive conclusion about the relationship between implant design and implant placement feasibility. Within the limitation, it is recommended to use implant systems having tapered designs and/or aggressive threads or apply drilling techniques such as under-drilling or osseodensification in the bone with poor bone quality in order to increase the primary stability [ 21 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Basic studies on various implant materials and with bisphosphonate administration are rare and therefore it is still unclear whether there are material-related differences in peri-implant hard and soft tissue [ 21 23 ]. Nevertheless, clinical studies of zirconia implants with healthy patients already showed positive outcome [ 24 30 ].…”
Section: Introductionmentioning
confidence: 99%